706. Impact of Infectious Disease Consultation on Management and Clinical Outcomes of Infective Endocarditis: Results of an interrupted time series analysis. (31st December 2020) - Okura, Takayuki; Iwata, Kentaro; Ohji, Goh
Abstract: Background: Infective endocarditis (IE) is associated with significant morbidity and mortality, and successful management requires expertise in both cardiac surgery and infectious disease (ID). However, the impact of ID consultation on clinical outcomes of IE is not clear. Methods: The present study was a quasi-experimental, interrupted time series analysis of the clinical outcomes of patients with IE before (April 1998–April 2008) and after (May 2008–March 2019) the establishment of an ID department at a tertiary care hospital in Japan. The primary outcome was clinical failure within 90 days, defined as a composite of all-cause mortality, unplanned cardiac surgery, new-onset embolic events, and relapse of bacteremia caused by the original pathogen. Results: Of 238 IE patients, 59 patients (25%) were treated in the pre-intervention period, and 179 patients (75%) were treated in the post-intervention period. Establishment of an ID department was associated with a 54% reduction in clinical failure (relative risk [RR], 0.46; 95% confidence interval [CI], 0.21–1.02; P=0.054) and a 79% reduction in new-onset embolic events (RR, 0.21; 95% CI, 0.07–0.71; P=0.01). In addition, the rate of inappropriate IE management significantly decreased (RR, 0.06; 95% CI, 0.02–0.22; P< 0.01). Segmented regression analysis for monthly rates of clinical failure. Table 1. Comparison of the clinical characteristics of the patients between the pre-intervention and post-intervention periods Table 2. Segmented regression analysis for primary and secondary outcomes Conclusion: Establishment of an ID department at a tertiary care hospital was associated with improved management, better clinical outcomes, and reduced embolic events in patients with IE admitted to the hospital. Disclosures: All Authors : No reported disclosures